2013
DOI: 10.3389/fmicb.2013.00372
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1/-2 and HIV-1 co-infections: retroviral interference on host immune status

Abstract: The human retroviruses HIV-1 and HTLV-1/HTLV-2 share similar routes of transmission but cause significantly different diseases. In this review we have outlined the immune mediated mechanisms by which HTLVs affect HIV-1 disease in co-infected hosts. During co-infection with HIV-1, HTLV-2 modulates the cellular microenvironment favoring its own viability and inhibiting HIV-1 progression. This is achieved when the HTLV-2 proviral load is higher than that of HIV-1, and thanks to the ability of HTLV-2 to: (i) up-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 184 publications
0
19
0
Order By: Relevance
“…The effect of HIV-1/HTLV-1 co-infection on the pathological conditions seems clearer and converges with a worsening of symptoms linked to HIV-1 or HTLV-1 infection [ 134 , 153 ]. Although the number of documented HIV-1/HTLV-1 co-infected cohorts remains low, it is believed that HTLV-1 worsens HIV-1 infection by accelerating progression to AIDS or increasing mortality [ 154 ].…”
Section: Hiv-1 and Htlv-1 Co-infectionsmentioning
confidence: 99%
“…The effect of HIV-1/HTLV-1 co-infection on the pathological conditions seems clearer and converges with a worsening of symptoms linked to HIV-1 or HTLV-1 infection [ 134 , 153 ]. Although the number of documented HIV-1/HTLV-1 co-infected cohorts remains low, it is believed that HTLV-1 worsens HIV-1 infection by accelerating progression to AIDS or increasing mortality [ 154 ].…”
Section: Hiv-1 and Htlv-1 Co-infectionsmentioning
confidence: 99%
“…On the other hand, it seems that HTLV-2 may confer certain immunological protection against HIV-1, delaying the natural history of the disease [125]. The proposed mechanism would be an interaction of the Tax-2 protein at several levels of the replicative cycle of HIV-1 and the alteration of several immunological processes [126].…”
Section: Hiv and Htlv1/2 Dual Infectionmentioning
confidence: 99%
“…Comparative studies of HTLV-1 and HTLV-2 have been aimed at identifying peculiar properties of HTLV-1 that may explain its oncogenicity. Cohort studies of HIV-infected persons have indicated that HTLV-2 might be protective against HIV-1 replication, although the role of HTLV-1 and 2 in HIV co-infection remains controversial [18].…”
Section: Introductionmentioning
confidence: 99%